Government Discretion of the Regional Election Implementation During Covid-19 Pandemic Through Technology Utilitization - Dani Habibi; Danang Ari Wibowo (Kanun Jurnal Ilmu Hukum, 2021)
The simultaneous regional elections held in 2020 in Indonesia encountered a problem. The constraints experienced are not due to a lack of supply materials for the elections or the absence of regulations on the regional elections, but to a condition experienced by the whole world, namely the COVID-19 pandemic outbreak. This research is included in normative research with a statutory and conceptual approach. This research aims to formulate the discretion that the government must carry out so that simultaneous regional elections are still carried out as a form of legal protection for the people regarding the right to vote and be elected in simultaneous regional elections, namely elections electronically with the use of technology and then the authors analyse and reconstruct Law Number 6 of 2020 concerning the simultaneous regional elections to formulate rules regarding the existence of an electronic election system to minimize the occurrence of population mobilization.